KEMANDIRIAN BELAJAR SISWA DALAM MENGIKUTI ALUR PROBLEM BASED LEARING DALAM PEMBELAJARAN - Iskandar Iskandar; Cicyn Riantoni (Institut Pendidikan Tapanuli Selatan, 2024)
Today's 21st century learning demands an increase in human resources who have high technological capabilities and an attitude of independence. So that education in schools is required to adapt the needs of human resources to the needs of the 21st century learning system. The purpose of this study was to see student learning independence in following the problem-based learning path in eyeglass learning. This study uses mixed methods with an explanatory model. The data collection instruments used were questionnaires and interview guidelines. The collected data were analyzed using quantitative descriptive. The results showed that the proportion of student learning outcomes tended to be in the good category with the proportion for males 52% and females 63%. However, there are still some obstacles that students experience in following the PBL learning flow, where these obstacles come from students, teachers and also supporting facilities and infrastructure. In addition, there is an influence between PBL and learning independence. The contribution of the influence of PBL on independent learning for male students is 75%, while for female students is 74%.